PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Setiawan, Pang michael dandy pratama (International Journal of Social Science and Business, 2020)
This study aims to analyze the effect of financial performance on company value with corporate governance as a moderating variable. This study uses purposive sampling which obtained 31 samples of manufacturing companies listed on the Indonesia Stock Exchange in the period 2015 ? 2018. The test results in this study prove that financial performance has a positive effect on company value and corporate governance is able to significantly strengthen the effect of financial performance on company value. Good and increasing corporate finance causes an increase in share prices and the number of shares outstanding so that the value of the company increases as well while managerial ownership as a proxy for moderating variable causes the company management to take appropriate and wise actions for the company?s survival so that the company?s financial performance increases so the value of the company increases too.